2015
DOI: 10.3109/00365521.2014.1003396
|View full text |Cite
|
Sign up to set email alerts
|

Liver stiffness and portal blood flow modifications induced by a liquid meal consumption: pathogenetic mechanisms and clinical relevance

Abstract: A low calories/low-volume meal is capable of significantly increasing LS regardless of the grade of stiffness, determining a reclassification rate of 17%. In presence of minimal or moderate stiffness, the increase of LS is significantly correlated with the augment of PBF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…32,33,34 The increase of liver stiffness after food intake is related to an increase of portal blood flow. 35,36 Concerning spleen stiffness, Han et al have shown its decrease after reducing portal hypertension in patients who underwent transjugular intrahepatic portosystemic shunt (TIPS). 37 Thus, it seems that tissue stiffness is changing with fluid pressure and with the content of fluid in the studied organs.…”
Section: Discussionmentioning
confidence: 99%
“…32,33,34 The increase of liver stiffness after food intake is related to an increase of portal blood flow. 35,36 Concerning spleen stiffness, Han et al have shown its decrease after reducing portal hypertension in patients who underwent transjugular intrahepatic portosystemic shunt (TIPS). 37 Thus, it seems that tissue stiffness is changing with fluid pressure and with the content of fluid in the studied organs.…”
Section: Discussionmentioning
confidence: 99%
“…[13] However, another study suggested a linear relationship between liver stiffness and portal flow in non-cirrhotic patients. [26]…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of the liver stiffness were performed on the right lobe of the liver, on a site localized by previous ultrasound evaluation, through the intercostal spaces with patient in supine position. Ten valid measurements were performed on each patient and only exams with a success rate of at least 60% and an interquartile interval <30% were considered reliable [ 33 ]. We excluded from the study conditions that technically prevented the execution of liver elastography (severe obesity, narrowness of intercostal spaces).…”
Section: Methodsmentioning
confidence: 99%